ALCOHOL PACKAGING RESTRICTIONS AND CONSUMER SUBSTITUTION BEHAVIOUR IN RIVERS STATE, NIGERIA: IMPLICATIONS FOR PUBLIC HEALTH POLICY (UNIZIK Journal of Marketing, 2026)
Spurred by the recent ban on the production and distribution of alcohol in sachets and small-sized containers, this study investigates the relationship between alcohol packaging restrictions and consumer substitution behaviour in Rivers State, Nigeria, with implications for public health policy. A descriptive survey research design was adopted, and data were collected from 384 respondents using a structured questionnaire administered through a mixed-mode approach. The sample size was determined using Cochran’s formula, while a multistage sampling technique was employed to capture both urban and rural consumers. Data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings indicate that alcohol packaging restrictions are primarily associated with alternative substance substitution, particularly toward energy drinks and non-alcoholic beverages, followed by product form switching from sachet alcohol to bottled or canned alternatives. A moderate behavioural shift was also observed in cross-category substitution, where consumers migrated from sachet alcohol to other alcoholic beverages such as beer. In contrast, movement toward informal or illicit alcohol sources, including locally distilled gin, remained statistically insignificant, suggesting continued reliance on formal distribution channels despite the restrictions. The study further reveals that income level significantly moderates the relationship between packaging restrictions and consumer substitution behaviour, with lower-income consumers exhibiting stronger behavioural adjustments due to affordability pressures. These findings suggest that packaging restrictions may influence the pattern and form of alcohol consumption rather than eliminate consumption entirely. The study concludes that alcohol packaging restrictions are associated with changes in consumer consumption patterns and may contribute to broader public health objectives when supported by effective enforcement, consumer education, and complementary harm-reduction interventions. The study, therefore, recommends stronger enforcement mechanisms, sustained consumer education, and complementary interventions aimed at promoting safer consumption alternatives.
Keywords: Alcohol packaging restrictions, Consumer substitution behaviour, Product form switching, Cross-category substitution, Informal/Illicit alcohol substitution, Alternative substance substitution.